PENGEMBANGAN KOMPETENSI KOMUNIKATIF BERBAHASA SISWA SMA/SMK - SUDARYANTO SUDARYANTO (Jurnal Kependidikan, 2006)
Abstract This study is to accelerate or develop communicative or functional competence in using Indonesian and English of General and Vocational Senior High School students through communicative approach. Several techniques are used. The Picture Cue Card technique is used for the students of the State Vocational Senior High School 3 Purwokerto, whereas the Feature Analysis technique is used for the students of General Senior High School of Abdi Negara of Muntilan. Retelling technique is used for the students of State Vocational Senior High School1 of Depok, whereas the Progressive technique is used for the students of the State General High School 7 of Yogyakarta. This research is a classroom action rsearch with communicative learning approach. The result show following: (1) Picture Cue Card thechnique can accelerate English ability. (2) Feature Analysis technique can accelerate the mastery of Indonesian vocabulary (3) Retelling technique can accelerate the ability in reading English texts (4) Progressive learning can accelerate the ability in writing in Indonesian. Keywords: picture cue cards technique, analysis feature, retelling, progressive learning,classroom action research.